Challenging Management of a Patient With Severe Bilateral Deep Vein Thrombosis - Mohanad Hamandi MD; Allison T. Lanfear; Seth Woolbert; Madison L. Bolin; Joy Fan; Michael William MD; Zoheb Khan; J. Michael DiMaio MD; Chadi Dib MD (SAGE Publishing, 2020)
Among patients with proximal iliofemoral deep vein thrombosis (DVT) and an elevated Villalta score, anticoagulation therapy alone may not be a sufficient management strategy in select cases. In this article, we report a case of severe bilateral iliofemoral DVT that resisted the standard treatment for DVT, requiring catheter-directed thrombolysis and subsequent mechanical thrombectomy.